Cardiac Magnetic Resonance Imaging in Patients with Acute Ischemic Stroke and Elevated Troponin: A TRoponin ELevation in Acute Ischemic Stroke (TRELAS) Sub-Study - Karl Georg Haeusler; Christoph Jensen; Jan F. Scheitz; Thomas Krause; Christian Wollboldt; Bernhard Witzenbichler; Heinrich J. Audebert; Ulf Landmesser; Jochen B. Fiebach; Christian H. Nolte; Matthias Endres; Hans-Christian Mochmann (Cerebrovascular Diseases Extra, 2019)
Background: Elevated high-sensitive cardiac troponin (hs-cTn) can be found in more than 50% of the patients with acute ischemic stroke. The observational TRoponin ELevation in Acute ischemic Stroke (TRELAS) study revealed that about 25% of all stroke patients with elevated troponin had a coronary angiography-detected culprit lesion affording immediate intervention, and about 50% of all patients did not have any obstructive coronary artery disease. Given the risk of procedure-related complications, the identification of stroke patients in urgent need of invasive coronary angiography is desirable. Methods: TRELAS patients were prospectively enrolled into this sub-study. In addition to conventional coronary angiography, a cardiac magnetic resonance imaging (MRI) at 3T was performed during the in-hospital stay after acute ischemic stroke to compare the diagnostic value of both imaging modalities. Results:Nine stroke patients (median age 73 years [range 58–87]; four females; median NIH Stroke Severity score on admission 4 [range 0–6] with elevated hs-cTnT [median 74 ng/L, interquartile range 41–247] on admission) completed cardiac MRI and underwent coronary angiography. The absence of MRI-detected wall motion abnormalities and/or late gadolinium enhancement in 5 stroke patients corresponded with the exclusion of culprit lesions or significant coronary artery disease by coronary angiography. Four patients had abnormal MRI findings, whereof 2 showed evidence of myocardial infarction and in whom coronary angiography demonstrated a >70% stenosis of a coronary artery. Conclusions: The TRELAS sub-study indicates that noninvasive cardiac MRI may provide helpful information to identify stroke patients with or without acute coronary syndrome. Our findings might help to select stroke patients in urgent need of coronary angiography.